LAWYER COMPETENCIES FOR ACCESS TO JUSTICE: TWO EMPIRICAL STUDIES - Marsden, Sarah; Buhler, Sarah (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
The definition and framing of legal competencies affects how lawyers learn and enact their roles and forms a necessary site of engagement in evaluating the relationship between law and justice. Drawing on two community-based studies with members of marginalized communities and lawyers and advocates who work with those communities, we outline the need for a transformation of the idea of legal competencies to emphasize relationality, critical reflection, and deep attention to context. We argue that such a change is a necessary precursor to meaningful engagement with access to justice by the legal profession.